Random Partner Name
Let's create a random partner: Jordan Lee, a high school mathematics teacher with a focus on algebra and calculus.
Question 1
Expression with Rational Exponents:
-
\( x^{\frac{3}{4}} \cdot x^{\frac{1}{2}} \)
Simplified form: \[ x^{\frac{3}{4} + \frac{1}{2}} = x^{\frac{3}{4} + \frac{2}{4}} = x^{\frac{5}{4}} \]
Expression with Radicals: 2. \( \sqrt{18} \)
Simplified form: \[ \sqrt{18} = \sqrt{9 \cdot 2} = \sqrt{9} \cdot \sqrt{2} = 3\sqrt{2} \]
Question 2
Expression: \[ x^{\frac{5}{6}} \cdot x^{\frac{1}{6}} \]
Step 1: Combine the exponents using the product of powers property: \[ x^{\frac{5}{6} + \frac{1}{6}} \]
Step 2: Add the exponents: \[ x^{\frac{6}{6}} \]
Step 3: Simplify: \[ x^1 = x \]
Question 3
Evaluate the Expressions:
- \( 4\sqrt{x^3} \)
- \( \frac{1}{x^{-1}} \) = \( x \)
- \( 10\sqrt{x^5 \cdot x^4 \cdot x^2} = 10\sqrt{x^{5 + 4 + 2}} = 10\sqrt{x^{11}} = 10x^{\frac{11}{2}} \)
- \( x^{\frac{1}{3}} \cdot x^{\frac{1}{3}} \cdot x^{\frac{1}{3}} = x^{\frac{1}{3} + \frac{1}{3} + \frac{1}{3}} = x^1 = x \)
Determine Equivalence:
- \( 4\sqrt{x^3} \) is not equivalent to \( x \) or \( 10x^{\frac{11}{2}} \).
- \( \frac{1}{x^{-1}} = x \) is equivalent to the fourth expression \( x \).
- \( 10\sqrt{x^5 \cdot x^4 \cdot x^2} \) (which simplifies to \( 10x^{\frac{11}{2}} \)) is not equivalent to any of the other expressions.
Justification:
- The expressions \( \frac{1}{x^{-1}} \) and \( x^{\frac{1}{3}} \cdot x^{\frac{1}{3}} \cdot x^{\frac{1}{3}} \) are equivalent, both simplifying to \( x \).
Question 4
Instructions for Exchange:
- Share the expressions and work for Question 1 with Jordan.
- Discuss findings:
- Ensure to simplify Jordan's expressions for Question 1, if needed.
- Review and critique Jordan's work on Question 2.
- Review and critique Jordan's work on Question 3, identifying any equivalences or errors.
Now you have a complete set of responses and instructions for engaging with your partner, Jordan Lee!